(untitled) (Nexus International Journal of Science and Education, 2024)
The study unfolded the of challenges of teacher-learner rapport and on reading engagement among Maco North District, Davao de Oro Schools Division. The study used non-experimental descriptive-correlational research design, utilizing adapted survey instrument to gather responses from the randomly selected teacher-respondents. Data gathered were treated using Mean scores with descriptive interpretation, Pearson r and Simple Linear Regression Analysis. Findings revealed that extent of challenges of teacher-learner rapport in terms of special needs students, teacher burn-out, transitions and mobility and diverse learning styes are oftentimes manifested; while, technology distractions is sometimes manifested, thus extensive, and, likewise, extent of reading engagement in terms of interactions in reading material, use of reading strategy and sustained focus are oftentimes manifested; independent reading choices is sometimes manifested, is extensive. There is a significant relationship between teacher-learner rapport and reading engagement. All domains of challenges of teacher-learner rapport in terms of diverse learning styles, technology destructions, special needs students, transitions and mobility, and teacher burnout significantly influenced reading engagement. Future research may explore effective interventions and strategies to overcome these challenges, considering cultural, socio-economic, and educational context variables.